2022
DOI: 10.3390/ani12162109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lonicera japonica and Radix Puerariae Crude Extracts on the Fecal Microbiome and Nutrient Apparent Digestibility of Finishing Pigs

Abstract: This study aims to investigate the influence of adding Lonicera japonica (L. japonica) and Radix Puerariae crude extracts and their mixture to the diet of finishing pigs on their fecal microbes and nutrient apparent digestibility. A total of 72 healthy Duroc × Landrace × Yorkshire crossbred barrows without significant differences in body weight (93 ± 2 kg) were selected and randomly divided into four groups (18 in each group). Three replicate pens per group (six pigs per pen) were used, and two pigs were evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Similarly, Zhang, Wang, et al (2018) found that the number of lactic acid bacteria in the colon of pigs fed with CGA diet increased significantly and the number of E. coli decreased significantly. A recent report showed that the addition of honeysuckle and pueraria crude extracts (CGA) to the diet of fattening pigs significantly increased the relative abundance of faecal microorganisms and increased the digestibility of protein and total phosphorus (Liu et al, 2022). Based on the above references, a schematic diagram of the effect of CGA on pig intestinal health was drawn (Figure 6).…”
Section: Research Progress Of Cga In Pig Industrymentioning
confidence: 99%
“…Similarly, Zhang, Wang, et al (2018) found that the number of lactic acid bacteria in the colon of pigs fed with CGA diet increased significantly and the number of E. coli decreased significantly. A recent report showed that the addition of honeysuckle and pueraria crude extracts (CGA) to the diet of fattening pigs significantly increased the relative abundance of faecal microorganisms and increased the digestibility of protein and total phosphorus (Liu et al, 2022). Based on the above references, a schematic diagram of the effect of CGA on pig intestinal health was drawn (Figure 6).…”
Section: Research Progress Of Cga In Pig Industrymentioning
confidence: 99%